2017
DOI: 10.1017/s1755773917000108
|View full text |Cite
|
Sign up to set email alerts
|

Stealth democracy and the support for new and challenger parties

Abstract: In the wake of the 2008 Great Recession, new and challenger parties have enjoyed electoral gains in some European countries. Political and economic disaffection have been pointed out as the main drivers of their electoral support. This article proposes voter’s stealth democracy attitudes, as defined by Hibbing and Theiss-Morse, as an additional driving force to account for this electoral change. We examine the case of Spain with a survey conducted after the far-reaching transformation of the party system, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 40 publications
5
39
0
2
Order By: Relevance
“…This problem of unequal representation (which we demonstrate empirically below) more generally reflects ways in which preferences for different forms of organization play out in terms of the character, scale, stability, and coherence of various political mobilization processes (Dahlberg-Grundberg, 2015;Kavada, 2013). Indeed, we may be entering an era in which different organization and participation preferences operate as forms of ideology that better distinguish voters on the far left and right than earlier distinctions about class or economic positions (Bengtsson & Mattila, 2009;Gauja, 2016;Lavezzolo & Ramiro, 2017).…”
Section: The Democratic Interface In the Electoral Arenamentioning
confidence: 99%
See 1 more Smart Citation
“…This problem of unequal representation (which we demonstrate empirically below) more generally reflects ways in which preferences for different forms of organization play out in terms of the character, scale, stability, and coherence of various political mobilization processes (Dahlberg-Grundberg, 2015;Kavada, 2013). Indeed, we may be entering an era in which different organization and participation preferences operate as forms of ideology that better distinguish voters on the far left and right than earlier distinctions about class or economic positions (Bengtsson & Mattila, 2009;Gauja, 2016;Lavezzolo & Ramiro, 2017).…”
Section: The Democratic Interface In the Electoral Arenamentioning
confidence: 99%
“…However, recent studies suggest that citizens on the right prefer 'stealth democracy' (Hibbing & Theiss-Morse, 2002) that favors efficiency and expert input over debate and direct participation (Bengtsson & Mattila, 2009;Bowler, Denemark, Donovan, & McDonnell, 2016;Lavezzolo & Ramiro, 2017;Webb, 2013). This would imply that engagement preferences continue to be compatible with the leader-centered and centralized organization of the vertical model.…”
Section: Organizational Preferences On the Rightmentioning
confidence: 99%
“…Other indicators that measure political trust or satisfaction with democracy are available for a shorter period. Further research may want to delve deeper into which indicator of political dissatisfaction drives new party support the most: political dissatisfaction, as we studied here (also see Vidal 2018), or other more complex indicators such as support for stealth democracy (Lavezzolo and Ramiro 2018) or voterlevel populist beliefs (Akkerman, Mudde, and Zaslove 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Different analyses have shown that both populist attitudes and economic evaluations have affected vote choices in West European countries (Fraile and Lewis-Beck 2014;Hernández and Kriesi 2016;van Hauwert and van Kessel 2017;Lavezzolo and Ramiro 2018;Andreadis et al 2018). We lack information, however, about the degree to which such attitudes have exerted any influence on party ideological positions.…”
Section: Introductionmentioning
confidence: 96%